2012
DOI: 10.1309/ajcpr3n3jmsylpfg
|View full text |Cite
|
Sign up to set email alerts
|

CD117 Expression Is a Sensitive but Nonspecific Predictor of FLT3 Mutation in T Acute Lymphoblastic Leukemia and T/Myeloid Acute Leukemia

Abstract: Others have suggested that CD117, or an immunophenotypic profile including CD117, can serve as surrogate for FLT3 mutation in T acute lymphoblastic leukemia (ALL), thereby guiding targeted therapy. We report the results of flow cytometry immunophenotypic analysis in 42 cases of T-ALL and T/myeloid acute leukemia also assessed for FLT3 mutation. CD117 was expressed in 21 (50%), and FLT3 was mutated in 8 cases (19%; 1 T-ALL and 7 T/myeloid). FLT3-mutated cases were terminal deoxynucleotidyl transferase (TdT)+/CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 16 publications
5
26
0
Order By: Relevance
“…In fact, T-ALL/ LBL with an ETP immunophenotype has a genetic profile more akin to normal hematopoietic and myeloid leukemic stem cells 33 and may carry FLT3-ITD mutation, a feature typically associated with AML. 34 TdT is normally expressed in committed T-lymphocytic progenitors. 35 TdT-negative T-ALL/LBL may be derived from an early stage of T precursors simply lacking TdT expression or from a later stage of precursors with a perturbed T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, T-ALL/ LBL with an ETP immunophenotype has a genetic profile more akin to normal hematopoietic and myeloid leukemic stem cells 33 and may carry FLT3-ITD mutation, a feature typically associated with AML. 34 TdT is normally expressed in committed T-lymphocytic progenitors. 35 TdT-negative T-ALL/LBL may be derived from an early stage of T precursors simply lacking TdT expression or from a later stage of precursors with a perturbed T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of 15 patients (47%) were positive for FLT3 mutations (mostly ITD), all of which were CD117 1 . 36 Array-based comparative genomic hybridization analysis in 12 patients with MPAL demonstrated that all patients had at least 1 abnormality, including deletions of CDKN2A, IKZF1, MEF2C, BCOR, EBF1, KRAS, LEF1, MBNL1, PBX3, and RUNX1. 27 …”
Section: Genetic Alterations In Mpalmentioning
confidence: 99%
“…Mutations of genes typical for leukemic cells were described in 12/31 (39%) patients with MPAL in Chinese study 14 . FLT3 mutation was reported in 7/15 (45%) patients with T/myeloid MPAL, with internal tandem duplication being the mechanism in 6/7 (86%) cases 24 .…”
Section: Molecular Biologymentioning
confidence: 99%